Is the aging human ovary still ticking?: Expression of clock-genes in luteinized granulosa cells of young and older women - Amnon Brzezinski; A. Saada; H. Miller; NA Brzezinski-Sinai; A. Ben-Meir (BMC, 2018)
Abstract Background It has been shown - mostly in animal models - that circadian clock genes are expressed in granulosa cells and in corpora luteum and might be essential for the ovulatory process and steroidogenesis. Objective We sought to investigate which circadian clock genes exist in human granulosa cells and whether their expression and activity decrease during aging of the ovary. Study design Human luteinized granulosa cells were isolated from young (age 18-33) and older (age 39-45) patients who underwent in-vitro fertilization treatment. Levels of clock genes expression were measured in these cells 36 h after human chorionic gonadotropin stimulation. Methods Human luteinized granulosa cells were isolated from follicular fluid during oocyte retrieval. The mRNA expression levels of the circadian genes CRY1, CRY2, PER1, PER2, CLOCK, ARNTL, ARNTL2, and NPAS2 were analyzed by quantitative polymerase chain reaction. Results We found that the circadian genes CRY1, CRY2, PER1, PER2, CLOCK, ARNTL, ARNTL2, and NPAS2, are expressed in cultured human luteinized granulosa cells. Among these genes, there was a general trend of decreased expression in cells from older women but it reached statistical significance only for PER1 and CLOCK genes (fold change of 0.27 ± 0.14; p = 0.03 and 0.29 ± 0.16; p = 0.05, respectively). Conclusions This preliminary report indicates that molecular circadian clock genes exist in human luteinized granulosa cells. There is a decreased expression of some of these genes in older women. This decline may partially explain the decreased fertility and steroidogenesis of reproductive aging.